Using Picture Exchange Communication System To Improve Speech Utterance Among Children With Autism - Widuri Jusoh; Rosadah Abd Majid (Department of Special Education, 2017)
Picture Exchange Communication System is a common augmentative communication system used on children with Autism Spectrum Disorder (ASD), which is one of the categories of developmental problems in social interaction, communication and behavior patterns. The aim of this study is to see an increase in the utterance of the word by students with autism using PECS. This study is an action research using quantitative descriptive on data collection. Observations were implemented over a period of four weeks to see the effectiveness of PECS using cartoon picture cards and cards real pictures to enhance the utterance of two primary school autism students. From the result shown, the application of PECS successfully stimulates utterance among the students. This study is expected to enhance the communication and social interaction development of children with autism and other children who have difficulty mastering the language.